2019
DOI: 10.1111/mve.12363
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure and rickettsias in Amblyomma ovale in areas of epidemiological interest for spotted fever in Brazil

Abstract: Amblyomma ovale (Ixodida: Ixodidae) Koch, 1844 is widely-reported in the neotropical region and is the main vector in the epidemic cycle of Rickettsia parkeri strain Atlantic rainforest, a bioagent of a milder variety of spotted fever (SF). Because species with wide geographical distributions are known to exhibit variations that influence their vectorial capacity, the present study aimed to analyze genetic diversity and rickettsia infection of A. ovale collected during the investigation and surveillance of SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
(59 reference statements)
2
23
0
3
Order By: Relevance
“…Based on previous studies [48][49], isolation by distance suggests that the populations are in equilibrium of migration and genetic drift at the spatial scale of Niigata Prefecture. Our results were congruent with a previous study of Amblyomma ovale that showed positive relationship of geographic and genetic distance at the spatial scale of the whole of Brazil whose main hosts for the immature stage are small rodents while tapir and jaguar in its adult stage [50]. In contrast, H. flava populations showed an absence of isolation by distance.…”
Section: Contrasting Population Genetic Structures Between H Flava Asupporting
confidence: 91%
See 1 more Smart Citation
“…Based on previous studies [48][49], isolation by distance suggests that the populations are in equilibrium of migration and genetic drift at the spatial scale of Niigata Prefecture. Our results were congruent with a previous study of Amblyomma ovale that showed positive relationship of geographic and genetic distance at the spatial scale of the whole of Brazil whose main hosts for the immature stage are small rodents while tapir and jaguar in its adult stage [50]. In contrast, H. flava populations showed an absence of isolation by distance.…”
Section: Contrasting Population Genetic Structures Between H Flava Asupporting
confidence: 91%
“…16S I. ovatus sequences showed genetic differentiation (pairwise F ST = 0.5-0.6) in few pairs of sampling locations as compared to the cox1 sequences which may be due to lower variability of the marker thus providing inadequate genetic variation for population genetic analysis, as previously observed in Amblyomma ovale [50] and Rhipicephalus microplus [56][57]. The low variability of the 16S in I. ovatus may not be sufficient to infer intraspecific relationship and is further supported by its low (nd = 0.001) nucleotide diversity as compared in cox1 I. ovatus (nd = 0.004).…”
Section: Contrasting Population Genetic Structures Between H Flava Amentioning
confidence: 68%
“…Amblyomma ovale hard ticks are located predominantly in South and Central America but can also be found in areas of the nearctic, particularly Mexico and the southern United States ( 1 , 2 ). Immature stages of this species parasitize many mammal and bird species, and adults complete their life cycle on artiodactyls and carnivores, particularly canids ( 1 , 3 ). A .…”
mentioning
confidence: 99%
“…ovale ticks have been collected predominantly in sylvatic areas, but because free-roaming dogs often enter sylvatic habitats and return to peridomestic settings with attached ticks, these ticks have become distributed into transitional and rural environments ( 3 ). In Brazil, this species has been implicated as the main vector of the Rickettsia parkeri strain Atlantic Rainforest, an eschar-associated spotted fever pathogen ( 3 , 4 ). Since its discovery, strain Atlantic Rainforest has been detected in other hard tick species, including A .…”
mentioning
confidence: 99%
“…These results are in agreement with the similarities found through the previously described BLAST search. In addition, R. rickettsii and R. felis were structured as distant groups, as seen in the phylogenetic study by Bitencourth et al (2019), which used a concatenated strategy with gltA, htrA, ompA, and ompB genes. Due to the intrinsic limitations of molecular identification using the gltA gene solely, the sequences of the present study were named as Rickettsia sp.…”
Section: Variablementioning
confidence: 99%